A Case for Pharmacare in Canada: Lessons Learned from the UK - Kilian, Alexandra; Fong, Emily; Halawa, Sara; Hughsam, Matthew; Li, Ben (The Meducator, 2016)
In 2014, total drug expenditure in Canada was $33.9 billion, of which a significant proportion (85%) was spent on prescribed drugs.1 Prescription drugs have become an integral component of modern medicine as they can help treat diseases and greatly improve quality of life.2 However, unlike most other countries with a universal health system, Canada does not universally cover prescription drugs.2 While some level of public drug coverage is provided by all provinces and territories in Canada, 58% of prescription drug costs are covered by private health insurance plans or out-of-pocket payments.2 As a result, there is growing interest among the Canadian public to implement a public drug insurance program, often termed “Pharmacare,” to improve access to prescription drugs.2 The United Kingdom (UK) has had a public financing system for health coverage in place, including prescription drugs, for decades. This article explores what Canada can learn from the UK’s successful universal drug coverage program.